A comparative accuracy of regularized and tension spline methods to estimate and model the surface water pH of Pulau Tuba, Langkawi, Kedah / Sharir Aizat Kamaruddin ... [et al.] - Kamaruddin, Sharir Aizat; Ahmad Nasir, Nor Atikah Husna; Rahim, Nur Syafiqah; Shuhaime, Norlin; Hashim, Mohd Akmal; Khazali, Ahmad Suhail; Abd. Aziz, Khairul Naim; Roslani, Muhammad Akmal (Faculty of Applied Sciences, 2021)
This research is conducted to assess the accuracy of spline interpolation methods to predict and model the surface water pH of Pulau Tuba, Langkawi, Kedah, Malaysia. In-situ sampling activities using pH-meter and Geographic Positioning Systems (GPS) were carried out during high tides and at noon in November 2018. The development of spatial models was constructed using Regularized and Tension spline methods. Then, validation of models was carried out to compare the observed and predicted values of pH using correlation analysis, regression analysis, and error analysis. The accuracy of the developed map was calculated using the overall accuracy equation. This research found that the regularized spline method had more accuracy in estimating surface water pH variability than the tension spline method. Pearson correlation coefficient (r), Coefficient of determination (R2 ), Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) were reported at 0.896, 0.803, 0.0265 and 0.0344 for the regularized spline method, respectively. The developed spatial model was then transformed into a map by adding map elements such as legend, title, north arrow, and scales for effective visualization. The developed map has an accuracy of 87.50%. The surface water pH was found at the range of 7-8. Low reading of pH is expected due to the addition of rainwater to the coastal water of Pulau Tuba, Langkawi, Kedah. The research outcomes would benefit government and non-government agencies to monitor the coastal and ocean acidification and the development of strategic policies and rules to reduce the impact of anthropogenic activities and climate changes for this area.